Improving Self-Regulated Learning and Creativity of Students through GeoGebra in Solving Spatial Geometry Problems - Indra Kurniawan; Andri Rahadyan (Mathematics Education Study Program, FKIP, Universitas Pasundan, 2022)
This study aims to determine the implementation of GeoGebra in solving problems to increase students' independence and creativity. The research subjects were 6 grade 12 students at SMA IPA HSPG Bekasi Odd Semester 2022/2023 Academic Year. This research method is qualitative, with data collection in task-based interviews. The main instrument in this study is the researcher and the auxiliary device, namely the problem-solving test (PST). Data analysis techniques in this study were carried out by (1) grouping data into independent learning and creativity categories, (2) presenting data in the form of narrative text, and (3) conducting analysis to conclude. There was an increase in learning independence in high-category students. Students were more enthusiastic about using GeoGebra in solving questions, and students' creativity has also increased by finding one new way. There was an increase in learning independence in moderate-category students. Students were increasingly enthusiastic about using GeoGebra in solving questions even though students were still unsure. Student creativity also increased by finding one new way, but it could have been better. There was an increase in learning independence in low-category students. Students started trying GeoGebra even though students could only make geometric shapes. There was no increase in student creativity.